A meta-analysis and genome-wide association study of platelet count and mean platelet volume in african americans. - Rehan Qayyum; Beverly M Snively; Elad Ziv; Michael A Nalls; Yongmei Liu; Weihong Tang; Lisa R Yanek; Leslie Lange; Michele K Evans; Santhi Ganesh; Melissa A Austin; Guillaume Lettre; et al. (PLoS Genetics)
Several genetic variants associated with platelet count and mean platelet volume (MPV) were recently reported in people of European ancestry. In this meta-analysis of 7 genome-wide association studies (GWAS) enrolling African Americans, our aim was to identify novel genetic variants associated with platelet count and MPV. For all cohorts, GWAS analysis was performed using additive models after adjusting for age, sex, and population stratification. For both platelet phenotypes, meta-analyses were conducted using inverse-variance weighted fixed-effect models. Platelet aggregation assays in whole blood were performed in the participants of the GeneSTAR cohort. Genetic variants in ten independent regions were associated with platelet count (N = 16,388) with p<5×10(-8) of which 5 have not been associated with platelet count in previous GWAS. The novel genetic variants associated with platelet count were in the following regions (the most significant SNP, closest gene, and p-value): 6p22 (rs12526480, LRRC16A, p = 9.1×10(-9)), 7q11 (rs13236689, CD36, p = 2.8×10(-9)), 10q21 (rs7896518, JMJD1C, p = 2.3×10(-12)), 11q13 (rs477895, BAD, p = 4.9×10(-8)), and 20q13 (rs151361, SLMO2, p = 9.4×10(-9)). Three of these loci (10q21, 11q13, and 20q13) were replicated in European Americans (N = 14,909) and one (11q13) in Hispanic Americans (N = 3,462). For MPV (N = 4,531), genetic variants in 3 regions were significant at p<5×10(-8), two of which were also associated with platelet count. Previously reported regions that were also significant in this study were 6p21, 6q23, 7q22, 12q24, and 19p13 for platelet count and 7q22, 17q11, and 19p13 for MPV. The most significant SNP in 1 region was also associated with ADP-induced maximal platelet aggregation in whole blood (12q24). Thus through a meta-analysis of GWAS enrolling African Americans, we have identified 5 novel regions associated with platelet count of which 3 were replicated in other ethnic groups. In addition, we also found one region associated with platelet aggregation that may play a potential role in atherothrombosis.